Job Satisfaction of Lecturer: A Systematic Literature Review Using the Prisma Method - Safria, Dhuha; Husen, Achmad; Suparno (Ilomata International Journal of Management, 2025)
Using a systematic literature review approach following the PRISMA guidelines, this study analyzed 20 scholarly articles published between 2020 and 2024 from various countries, focusing on the job satisfaction of lecturers. To ensure the quality of the included studies, only articles indexed in Scopus Q1, Q2, and Q3 were considered using the Watase UAKE database. The objective of this study is to provide a comprehensive understanding of the context and theoretical foundations employed in these studies. In terms of context, all analyzed articles used lecturers as their research subjects. Regarding theoretical foundations, Herzberg's two-factor theory is the most frequently used framework. This study also maps the variables that can be antecedents and consequences of lecturers' job satisfaction. The findings of this study are expected to contribute to the development of more effective policies for enhancing the job satisfaction of lecturers.